Fundamental of engineering mechanics - Nag, Debabrata (Chhaya Prakashani, 2010)
Fundamental of engineering mechanics / Nag, Debabrata. -- Kolkata: Chhaya Prakashani, 2010 620.1 N147e2 2nd ed. No. of Copies : 1